2015
DOI: 10.1186/s12933-015-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity and long-term mortality in patients with acute myocardial infarction with and without diabetes mellitus: results from the MONICA/KORA myocardial infarction registry

Abstract: BackgroundParadoxically, beneficial effects of overweight and obesity on survival have been found in patients after cardiovascular events such as acute myocardial infarction (AMI). This obesity paradox has not been analyzed in AMI patients with diabetes even though their cardiovascular morbidity and mortality is increased compared to their counterparts without diabetes. Therefore, the objective of this long-term study was to analyze the association between body mass index (BMI) and all-cause mortality in AMI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
3
27
1
Order By: Relevance
“…In prospective clinical studies, overweight or obese individuals have increased rates of cardiovascular diseases [1, 3, 41], contributing to a 2–3 fold increase in overall mortality relative to normal weight individuals[1, 7, 15, 32, 49, 51]. In addition to a direct link with occlusive vascular disease, obesity is strongly associated with impairment of systolic and diastolic function and the development of cardiac fibrosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In prospective clinical studies, overweight or obese individuals have increased rates of cardiovascular diseases [1, 3, 41], contributing to a 2–3 fold increase in overall mortality relative to normal weight individuals[1, 7, 15, 32, 49, 51]. In addition to a direct link with occlusive vascular disease, obesity is strongly associated with impairment of systolic and diastolic function and the development of cardiac fibrosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The MONICA/KORA study with 4,504 patients after MI demonstrated the relationship between obesity and CV outcomes regarding the presence of diabetes during 6 years. Higher BMI decreased the risk of long-term survival in patients without diabetes, although diabetes attenuated the protective role of obesity [23].…”
Section: Discussionmentioning
confidence: 94%
“…DM confers increased in-hospital mortality risk both in the ST-elevation myocardial infarction (STEMI) and the non-STEMI (NSTEMI) patients 19 . Moreover, this dismal prognosis of patients with AMI and DM is not related to the body mass index, i.e., "obesity paradox" is not relevant to them (in contrast to the AMI patients without DM) 20 . Indeed, a meta-analysis of 21,759 DM patients (~29% of them were insulin-treated) revealed that both short-term and long-term mortality, and the incidence of new AMI, target lesion revascularization, major adverse cardiac effect (MACE), and stent thrombosis were significantly more frequent in the insulin-treated DM patients 21 .…”
Section: Introductionmentioning
confidence: 94%